Red cell distribution width and mean platelet volume as mortality markers in patients with COVID-19: a retrospective cohort study - Kiliç, Jehat; Alakuş, Ömer F; Solmaz, İhsan (The Journal of Infection in Developing Countries, 2026)
Introduction: This study investigates RDW and MPV as simple, cost-effective markers linked to increased mortality in COVID-19, highlighting their potential prognostic value in viral infections. Methods: This retrospective observational study examined hospitalized COVID-19 patients from 2020 to 2022, assessing clinical outcomes such as ICU admission, hospital stay duration, and mortality. It focused on the prognostic value of Red Cell Distribution Width (RDW) and Mean Platelet Volume (MPV), investigating whether elevated levels of these markers could serve as accessible indicators of mortality risk. Results: The mean age at diagnosis among patients was 48.07 ± 17.33 years. The mean hospital stay was 5.82 ± 5.44 days. Among 1,810 patients, elevated Red Cell Distribution Width (RDW > 15%) and Mean Platelet Volume (MPV > 11.5 fL) were associated with significantly higher mortality rates (p < 0.01 and p = 0.014, respectively). Logistic regression analysis identified age, male sex, length of hospital stay, WBC count, RDW-CV, glucose, ferritin, and low albumin as independent predictors of mortality. Conversely, MPV, D-dimer, creatinine, calcium, and ALT were not significant mortality predictors. These findings suggest that routine markers, particularly RDW and WBC, may serve as accessible and cost-effective tools for early risk stratification in COVID-19 patients, while others, like MPV, may have limited independent prognostic value in this context. Conclusions: RDW and MPV, routinely available from blood tests, may help identify early clinical deterioration, supporting timely interventions to improve outcomes.